Interfacial Properties and Fragmentation Process in ZnO Nanowire Coated Hybrid Carbon Fiber Composite: A Multiscale Modeling Approach. Issue 10 (27th July 2022) - Marashizadeh, Parisa; Abshirini, Mohammad; Saha, Mrinal C.; Huang, Liangliang; Liu, Yingtao
Abstract: A multiscale modeling framework is developed to investigate the effect of ZnO nanowires (NWs) on the fiber/matrix interface, and the fiber fragmentation mechanism of ZnO NW coated single fiber composites (SFC). Atomistic traction–separation analysis is conducted using molecular dynamics simulation technique to evaluate the interface properties between the functionalized carbon fiber surface and ZnO NW/polymer matrix. The results indicate that incorporating ZnO NW can significantly enhance interface stiffness, strength, and fracture energy. The results obtained in opening and sliding modes are implemented in the cohesive zone model to simulate the interface at the mesoscale. Microhomogenization analysis is performed on a representative volume element containing ZnO NW reinforced polymer matrix to determine the effective material properties of the enhancement layer. The interface and enhancement layer properties are imported into the macroscale hybrid SFC model. Single fiber fragmentation analysis is performed employing user material (UMAT) subroutine and ABAQUS finite element analysis package. Simulation results demonstrate that the load is transferred more efficiently from matrix to fiber in the hybrid than in the bare fiber model. The fiber fragmentation is increased in the hybrid composite structure, resulting in up to 100% improvement in interfacial shear strength of SFC incorporating ZnO NW. Abstract : A multiscale modeling framework is developed to evaluate interfacial properties and fiber load transfer efficiency in hybrid carbon fiber composite. The interfacial properties are obtained from molecular dynamics simulation and implemented in the cohesive zone model. The finite element analysis shows that fiber fragmentation is increased by 73% incorporating synthesized nanowires, indicating enhanced load transfer capabilities of hybrid composite.